2019
DOI: 10.1016/j.heliyon.2019.e01469
|View full text |Cite
|
Sign up to set email alerts
|

Heat transfer enhancement in the boundary layer flow of hybrid nanofluids due to variable viscosity and natural convection

Abstract: The aim of the current work is to explore how heat transfer can be enhanced by variations in the basic properties of fluids in the presence of free convection with the aid of suspended hybrid nanofluids. Also, the influence of the Laurentz force on the flow is considered. The mathematical equations are converted into a pair of self-similarity equations by applying appropriate transformations. The reduced similarity equivalences are then solved numerically by Runge-Kutta-Fehlberg 45 th -o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
68
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 154 publications
(76 citation statements)
references
References 31 publications
8
68
0
Order By: Relevance
“…The influence of dissimilar physical parameters in the case of copper-aluminum oxide-water hybrid nanofluid phase and nanofluid phase on momentum, heat measure, surface drag coefficient, and rate of heat transfer is presented through various graphs in Figures 2 to 8. The physical characteristics of both nanoparticles and hybrid nanoparticles are displayed in Tables 1 to 4. A comparison between previously published results 18 and the present results for the coefficient of surface drag and Nusselt number is shown in concluded from Table 5A,B that the skin friction coefficient and rate of heat transfer increase with rising values of B and Pr numbers, respectively. Moreover, the drag coefficient and Nusselt numbers are higher in case of hybrid nanofluid as compared with mono-nanofluid (Cu-water).…”
Section: Resultssupporting
confidence: 83%
See 2 more Smart Citations
“…The influence of dissimilar physical parameters in the case of copper-aluminum oxide-water hybrid nanofluid phase and nanofluid phase on momentum, heat measure, surface drag coefficient, and rate of heat transfer is presented through various graphs in Figures 2 to 8. The physical characteristics of both nanoparticles and hybrid nanoparticles are displayed in Tables 1 to 4. A comparison between previously published results 18 and the present results for the coefficient of surface drag and Nusselt number is shown in concluded from Table 5A,B that the skin friction coefficient and rate of heat transfer increase with rising values of B and Pr numbers, respectively. Moreover, the drag coefficient and Nusselt numbers are higher in case of hybrid nanofluid as compared with mono-nanofluid (Cu-water).…”
Section: Resultssupporting
confidence: 83%
“…The governing conservation equations (ie, mass, momentum, and energy) with hybrid nanofluid flow problem can be expressed as 18,41…”
Section: Mathematical Formulationmentioning
confidence: 99%
See 1 more Smart Citation
“…Combination of CNTs into Anormall2normalO3 develops heat‐conducting capacity of the base liquid, which was discussed by Nuim Labib et al Bahiraei et al explored the incorporation of graphene and Ag nanoparticles, which can be used as coolant. Likewise, numerous analysts have demonstrated that the thermal boundary of a liquid can be upgraded by considering a solitary and two nanoadded substances …”
Section: Introductionmentioning
confidence: 99%
“…The aluminum oxide nanoparticle blended with carbon nano tubes (CNTs)/water nanofluids was used by Nuim Labib et al They analyzed numerically that the convective heat transfer performance was increased very much by using a hybrid nanofluid. Very recently, Manjunatha et al analyzed the variable properties of a hybrid nanofluid. Contemporary mathematicians have carried out research in the same field under different physical conditions …”
Section: Introductionmentioning
confidence: 99%